Laparoscopic appendectomy during the third trimester: Case presentation and literature review. Issue 4 (4th January 2018) - Iwamura, Sena; Hashida, Hiroki; Yoh, Tomoaki; Kitano, Shoichi; Mizumoto, Motoko; Kitamura, Koji; Kondo, Masato; Kobayashi, Hiroyuki; Kaihara, Satoshi; Hosotani, Ryo
Abstract: Acute appendicitis is the most common general surgical problem encountered during pregnancy. Laparoscopic appendectomy (LA) is widely accepted as a minimally invasive procedure for acute appendicitis. However, LA during the third trimester is associated with problems, including technical difficulty, risk of preterm delivery, and fetal loss. We successfully managed three cases of LA during the third trimester between 2011 and 2016. None of the cases required conversion to an open procedure, and none of the patients had postoperative complications and/or fetal loss. We reviewed the literature using the PubMED database from 2007 to 2016 to acquire further evidence and identified 6 reports and 17 cases. The conversion rate was 11.8% (2 cases), the complication rate was 6.67% (1 case), and the preterm delivery rate was 20% (3 cases); no fetal loss was observed. Our study and literature review highlights the role of LA as a potentially feasible treatment approach for appendicitis during the third trimester.